2011
DOI: 10.1539/joh.11-0045-oa
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Respirable Flour Dust and Gliadin in Wheat Flour Mills

Abstract: Department of Biochemistry and Nutrition, Faculty of Medicine, Hamadan University of Medical Sciences, Iran-Objectives:The aim of this study was to determine the concentrations of respirable flour dusts and gliadin as well as gliadinspecific serum antibodies in exposed workers of Hamadan wheat flour mill factories. Methods: Blood samples from 95 exposed workers and 80 air samples from flour packing, husk packing, flour production and wheat unloading areas were collected. Respirable flour dust density was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…Such exposure levels appeared to be comparable or lower than those found in other countries. For example, the total ambient dust concentration of 0.33 mg/m 3 was reported among 68 bakers in Norway ( 28 ), whereas a concentration of 1.56 mg/m 3 was recorded from flourmills in Iran ( 29 ). Moreover, significantly higher levels of dust were evident for dough makers in comparison to those working in other areas of a mill factory ( 12 ) which is consistent with the findings of the present case study and was also reported elsewhere ( 11 , 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such exposure levels appeared to be comparable or lower than those found in other countries. For example, the total ambient dust concentration of 0.33 mg/m 3 was reported among 68 bakers in Norway ( 28 ), whereas a concentration of 1.56 mg/m 3 was recorded from flourmills in Iran ( 29 ). Moreover, significantly higher levels of dust were evident for dough makers in comparison to those working in other areas of a mill factory ( 12 ) which is consistent with the findings of the present case study and was also reported elsewhere ( 11 , 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…[1,8,9] In previous studies, it was observed that the amount of serum antigen in the group exposed to flour dust has a significant difference comparing to control group. [10] Breathing flour dust can induce allergy and chronic respiratory problems like asthma. [11,12] The outbreak ORIGINAL ARTICLE of respiratory symptoms and chronic obstruction of the airways are observed in the workers exposed to heavy flour dust [13][14][15][16] and significant reduction of some pulmonary function parameters such as forced vital capacity (FVC), VC, forced expiratory volume in the first second (FEV 1 ), and peak expiratory flow rate (PEFR) is observed in the individuals exposed to dust.…”
Section: Introductionmentioning
confidence: 99%
“…pISSN 1858-1196 eISSN 2355-3596 function of industrial workers, one of which is impaired lung function (Khodadadi et al, 2011).…”
mentioning
confidence: 99%